Search For Existence Of Frank Moses In Red Movie Directed By Robert Schwentke (2010): An Existentialist Approach - Hayati, Yunita Nurul (2012)
The object of the research is a movie entitled Red. The major problem of her study is how search for existence of Frank Moses in Red movie directed by Robert Schwentke based on Existentialist approach. Therefore, the study analyzes the play in term of it structural elements of the play and based on the existentialist approach. These studies belong to qualitative study. The writer uses two data sources: they are primary data sources and secondary data sources. The primary data source is the movie. Meanwhile, the secondary data are taken from several references such as essays, articles, commentaries, website about the movie, reader's review, and others even about the author or existentialist material to support the subject matter. The method of the data collection is library research by collecting both primary and secondary data. The technique of data analysis is descriptive analysis based on Existentialist approach. The study comes to the following conclusions. FBased on the structural analysis of each element, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sounds and editing related to each other and form the unity into good quality of a movie.